Development Of Web-Based E-Learning Media On Equation Materials And Quadratic Function: Pengembangan Media Pembelajaran E-Learning Berbasis Website pada Materi Persamaan dan Fungsi Kuadrat - Orlando Nguru Armando Gianfrancho; Dwi Ferdiani Rosita (FPMIPA IKIP PGRI Bali, 2020)
Abstract: This study aims to develop website-based e-learning media. This media is an online or online learning media created by using the PHP (Personal Home Page) programming language and can be accessed via a PC (Personal Computer) or Mobile via a browser. The addition of the latex feature makes it easier for users to use symbols and mathematical formulas. While the chat feature makes it easy for students to consult the material with the teacher by online. The main purpose of the study is to determine the level of validity, feasibility and effectiveness of website-based e-learning media on the subject matter of equations and quadratic functions. This study uses a Research and Development (R&D) with a 4D model. The stages of the 4D development model are as follows: (1) Define, (2) Design, (3) Development, and (4) Dissemination. The validity level is based on the validator of media, materials and learning experts getting successively 4.50 media experts, 4.58 materials experts, and 4.36 learning experts. These results indicate that the media is very valid to be used as a learning media. In a small group trial with subjects as many as six students of Class XI Vocational School, students obtained 4,34 of the feasibility results and categorized as very feasible. In a large group trial with a trial subject of 20 students of Class XI Vocational School, the effectiveness of the media was obtained through the test with a percentage value of 95 %. Key Words : E-learning, Website, Research and Development